PEMANFAATAN SOLAR SEL DAN BUDIDAYA PERIKANAN SEBAGAI UPAYA MENUJU KEMANDIRIAN FINANSIAL DI SEKOLAH KAMI - Murie Dwiyaniti; Riandini Riandini; Eddy Supriyono (LP2M Universitas Hasanuddin, 2020)
Utilization of Solar Cells and Fisheries Culture as Efforts Towards Financial Independence in Sekolah KAMIAbstract. Sekolah Kami is a non-profit school that provides free non-formal education to scavengers and poor children. This school is located in the middle of scavenger shanties and landfills located in Pemulung Village, Bintara Jaya Village, West Bekasi District, Bekasi City. As an informal school that is managed independently, it requires substantial funding for operations. So far, funding has only relied on donors and the personal money of the School owner. So that the purpose of community service, strive for schools to obtain sustainable income for school operations by utilizing solar cells and aquaculture. The method consists of two stages, namely, build physical capital in the form of fish ponds and solar cell electricity sources; train and assist teachers in Sekolah Kami so that they can manage the facilities and infrastructure built. The results of this activity are the construction of fish ponds with 3x1x0.8 meters of cast cement with two ponds for catfish and tilapia, the realization of DC power sources from renewable energy, namely solar cells with 300 WP power for garden lighting, two pond pumps and an aquaponics pump, and aquaponics are built to grow mustard and watercress, and trained teachers can manage everything well. Good yields and sold in the market indicate this. Money from the sale has been used for school operations and buying fish seeds.Keywords: Catfish cultivation, tilapia, financially independent, solar cells, Sekolah Kami.Abstrak. Sekolah Kami merupakan sekolah nonprofit yang menyediakan pendidikan gratis non formal kepada anak-anak pemulung dan dhuafa. Sekolah ini terletak di tengah lapak pemulung dan tempat pembuangan sampah yang berlokasi di Kampung Pemulung Kelurahan Bintara Jaya, Kecamatan Bekasi Barat, Kota Bekasi. Sebagai sekolah informal yang dikelola secara swadaya sangat memerlukan dana yang cukup besar untuk operasional. Selama ini pembiayaan hanya mengandalkan donatur dan uang pribadi pemilik Sekolah. Pengabdian masyarakat ini bertujuan mengupayakan agar sekolah mendapatkan pemasukan secara berkelanjutan untuk operasional sekolah dengan memanfaatkan solar sel dan perikanan budidaya. Metode yang dilakukan terdiri dari dua tahap, yaitu membangun modal fisik berupa kolam ikan dan sumber listrik solar sel; melatih dan melakukan pendampingan untuk guru di Sekolah Kami agar dapat mengelola sarana dan prasarana yang dibangun. Hasil kegiatan ini adalah terbangunnya kolam ikan dengan bahan semen cor berukuran 3x1x0,8 meter sebanyak dua kolam untuk ikan lele dan nila, terwujudnya sumber listrik DC dari energy terbarukan, yaitu solar sel dengan daya 300 WP untuk penerangan taman, dua buah pompa kolam dan satu buah pompa aquaponik, dan terbangunnya aquaponik untuk menanam pokcay dan selada air, serta guru-guru yang telah dilatih dapat mengelola semuanya dengan baik. Hal ini ditandai dengan hasil panen yang cukup baik dan laku dipasaran. Uang hasil penjualan telah digunakan untuk operasional sekolah dan membeli bibit ikan dan pakan. Kata Kunci: Budidaya lele, nila, solar sel, Sekolah Kami.